The Effect of Government Policy on Infrastructure Priorities on the Profitability of Construction Companies in Indonesia 2011-2019 - Rifai, Ahmad; Irawan, Tony; Indrawan, Dikky (Faculty of Economics and Business, Universitas Gadjah Mada, 2024)
Introduction/Main Objective: The Indonesian government's policy of prioritizing the acceleration in infrastructure development will certainly have an impact on construction companies. Background of the Problem: This research aims to determine the influence of internal and external company factors on the profitability of companies in the building construction subsector. Novelty: This research analyzes the impact of increasing the government's infrastructure budget on the profitability of building construction subsector companies. Research Method: This research uses panel data regression analysis with annual financial report data from building construction subsector companies listed on the Indonesia Stock Exchange for the period from 2011 to 2019, which is divided into the period before the infrastructure sector became the focus of development (2011 to 2014) and after (2015 to 2019). Profitability is measured using the return on assets. The external factors are measured using the infrastructure budget and inflation, while the internal factors are measured using company size, liquidity, leverage, cash turnover, working capital turnover and receivables turnover. Findings/Results: This research concludes that the infrastructure budget, company size, and liquidity do not have a significant positive effect on company profitability, while inflation does not have a significant negative effect on profitability. Furthermore, cash turnover, working capital turnover, and account receivable turnover have a significant positive effect on profitability, while leverage has a significant negative effect on profitability. Conclusion: This research shows that companies should periodically review the impact of loans and always maintain the composition of their funding, according to their needs. Meanwhile, the government needs to evaluate the auction process, and sharpen its alternative infrastructure project funding strategies.